Numerical investigation of the effect of ocean depth variations on the dynamics of a ship mounted two-DoF manipulator system - Mohamad Luthfi Ramadiansyah; Edwar Yazid; Cheng Yee Ng (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2022)
The dynamics of a ship need to be considered in the development of a manipulator system that will be applied to the ocean-based operation. This paper aims to investigate the effect of ocean depth variations on the ship motion as disturbances to a ship-mounted two-DoF (Degrees of Freedom) manipulator joint torque using an inverse dynamics model. Realization is conducted by deriving the mathematical model of a two-DoF manipulator system subject to six-DoF ship motion, which is derived by using Lagrange-Euler method. It is then combined with numerical hydrodynamic simulation to obtain the ship motions under ocean depth variations, such as shallow (50 m), intermediate (750 m), and deep (3,000 m) waters. Finding results show that randomness of the ship motions appears on the manipulator joint torque. In the azimuth link, maximum joint torque is found in shallow water depth with an increment of 8.271 N.m (285.69 %) from the undisturbed manipulator. Meanwhile, the maximum joint torque of the elevation link is found in intermediate water depth with an increment of 53.321 N.m (6.63 %). However, the difference between depth variations is relatively small. This result can be used as a baseline for sizing the electrical motor and developing the robust control system for the manipulator that is mounted on the ship by considering all ocean depth conditions.